Income diversification in the banking sector and earnings volatility: Evidence from Kenyan commercial banks - Josephat Mboya Kiweu (Kenya Bankers Association (KBA), 2012)
This paper investigates whether diversification of income sources for Kenyan banks leads to better earnings and reduced individual bank and systemic risks. The study seeks to analyze the extent to which observed shift toward fees income generating activities has improved bank performance and reduced volatility of revenue. The findings show that there are few benefits, if any, to be expected from income diversification from traditional banking although there is growing importance of non-interest income during the study period 2000 - 2010. The benefits of the evolution of non-interest income do not seem to fully offset the increase in risk that come with fee based income. A positive correlation between net interest income and non-interest income seems to exist, a finding that suggests that non-interest income may not be used to stabilize total operating income. The findings also reveal that lending rates are significantly correlated with net interest income, and the relationship is negative meaning that more lending takes place when interest rates are favorable.
Keywords: 330